Implementation of the E-Ticket System in the Prosecution of Traffic Violations in Cirebon City - Dhelfa Nur Fadilah; Indri Anzani; Sri Wulandari; Aghnia Dian Lestari (Pusat Publikasi Nusantara, 2024)
This study aims to analyze the application of the E-Ticket system in prosecuting traffic violations in Cirebon City. E-Tilang is an electronic ticketing system implemented by the Indonesian National Police (Polri) in an effort to enforce traffic law and order. The research method used is a qualitative method with data collection techniques through observation, interviews, and documentation. The informants in this study were the Head and Members of the Cirebon City Police Traffic Unit. The results showed that E-Tilang in Cirebon City has not run optimally. Some of the obstacles faced are accountability such as limited human resources in the police who only have 22 members of Satlantas, lack of socialization to the public and the number of people unfamiliar with technology so that E-Tilang is considered complicated. In terms of centralization such as the lack of E-Tilang camera devices installed, and the inaccuracy of vehicle ownership data that has not been changed. The security of violator data is an important concern. E-Tilang camera devices are planned to be used in the future, along with the improvement of the mobile E-Tilang system.